U.S. Antarctic Policy [microform] : hearings before the Subcommittee on Oceans and International Environment, Committee on Foreign Relations, United States Senate, Ninety- Fourth Congress, first session. - United States. Congress. Senate. Committee on Foreign Relations. Subcommittee on Oceans and International Environment. (Washington : U.S. G.P.O., 1975)
Reuse of record except for individual research requires license from Congressional Information Service, Inc. "May 15, 1975." CIS Microfiche Accession Numbers: CIS 75 S381-18 CIS Index 1975. Microfiche. Mode of access: Internet.